Analysis of Women's Rights in Islam: Education and Gender Equality Perspective - Yondrizal; Rusydi. AM; Sri Wahyuni; Rismalaini (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
Objective: This study aims to analyze the guarantee of women's rights in Islam with a focus on education and gender equality. This study distinguishes Islamic normative teachings from social practices influenced by patriarchal culture. The goal is to build a contextual understanding that is gender-correct. Theoretical framework: The theoretical framework rests on the principles of justice ('adl) and benefit (maṣlaḥah) in Islam. Gender equality is understood as equality of dignity and responsibility, not absolute equal roles. Education is positioned as an instrument of social justice. Literature review:  women's studies in Islam are dominated by normative-theological approaches and patriarchal critiques. However, the integration of Islamic education and gender equality is still limited. This research fills the gap integratively and contextually. Methods: The research uses qualitative methods with descriptive-analytical and normative-conceptual approaches. Data was obtained through literature studies from the Qur'an, Hadith, tafsir, and scientific articles. The analysis was carried out thematically. Results: The results of the study affirm that Islam guarantees women's rights, including education and social roles, without discrimination. The inequality that occurs stems from biased interpretations and patriarchal culture. Gender equality is based on justice and benefits. Implications: The findings underscore the urgency of Islamic education from a gender justice perspective. Practically, these results are relevant for the development of an inclusive Islamic curriculum and discourse. Theoretically, this study enriches the study of Islam and gender. Novelty: The novelty of research lies in the contextual integration of women's rights, education, and gender equality. This study affirms Islamic normativity while criticizing distorted social practices. This framework offers an applicable understanding.